The metabolome of human milk is altered differentially by Holder pasteurization and high hydrostatic pressure processing - Tran, Léa Chantal; Marousez, Lucie; De Lamballerie, Marie; McCulloch, Scott; Hermann, Emmanuel; Gottrand, Frédéric; Ley, Delphine; Lesage, Jean (Frontiers in Nutrition, 2023)
The milk metabolome is composed of hundreds of molecules that can impact infant development. In preterm infants, sterilized donor milk (DM) is frequently used for their feeding. We aimed to identify differences in the metabolome of DM after two types of milk sterilization: the Holder pasteurization (HoP) and a high hydrostatic pressure (HP) processing. DM samples were sterilized by HoP (62.5°C for 30 min) or processed by HP (350 MPa at 38°C). 595 milk metabolites were analyzed using an untargeted metabolomic analysis. Both treatments differentially altered several classes of compounds. The major changes noted included decreased levels of free fatty acids, phospholipid metabolites, and sphingomyelins. Decreases were more strongly noted in HP samples rather than in HoP ones. Both HoP and HP treatments increased the levels of ceramides and nucleotide compounds. The sterilization of human milk altered its metabolome especially for lipids.